Analisis Kecenderungan Mengkonsumsi Marjinal dan Faktor-Faktor Yang Mempengaruhi Konsumsi Masyarakat Jawa Timur - Rohmaniyah Rohmaniyah; Slamet Subari (Fakultas Pertanian Universitas Veteran Bangun Nusantara Sukoharjo, 2017)
ABSTRACTThe purpose of this research is (1) to know the macro economic factors that influence the consumption of East Java society, (2) to analyze the marginal propensity to consume, (3) to discuss the consumption pattern of the East Java community. Multiple linear regression method is used to answer the first objective, the second objective is calculated using the MPC formula, while the third goal is analyzed through consumption expenditure table. The result of the research shows that income and interest rate influence the consumption of East Java society with coefficient value of 0,827 and 0,334 respectively. This shows that if there is increase of income and Interest rate of 1% then consumption will increase by 0.827 and 0.334. The value of East Java MPC ranges from -0.004 - 0.57 to an average of 0.240 (24%), this show that 24% of East Java's income is used for consumption, while the remaining 76% is used for consumption purposes. East Java community consumption pattern shows consumptive pattern to non food consumption with percentage equal to 54,12%. Keywords: East Java, Consumption, MPC